The Scene Cafe and Bistro / Mohamad Afiq Zuber ... [et al.] - Zuber, Mohamad Afiq; Abdul Wahab, Mohd Fariz Azwan; Sutiman, Muhammad Shaffuan; Razak, Nabilah; Abdul Haris, Nurita (2010)
The planning of the cafe that more focus on the franchises because there is the Worldwide Franchising Statistics (1995) where the consultancy surveyed state that the franchising in Malaysia do not very developed as compared to the other country such as United States and Japan. According to the author of research, Vitor F.C Goncalves & etc .• "The presence of international franchise systems is dominant, but a small number of local concepts were developed and some have already started international operations". However, it is not easy to develop a small business while have to compete with other franchising competitors such as Mc Donalds, KFC, Pizza Hut and other cafes. According to it, The Scene Cafe and Bistro have its own operational strategies and the most importantly how the concepts will be. We want to have an upscale, relaxing and leisure interior design in order to attract and keep customers. In addition, the cafe will be facilitating with innovative environment such as the affordable access to the internet or online services, reading section, and a partition for the gamers. Such as the Cafe Jubilee in Malta (1998), it is the first chain of cafe/bistro that was totally conceived locally by itself. In the business proposal of The Scene Cafe and Bistro is actually focus on the local operational to successfully stand with its own strategic partnership. By becoming The Scene Cafe and Bistro, the clients will satisfy to enjoy the food and drink in a unique homely environment. Why we choosing the franchise? This is because the food industries are becoming increasingly popular that make high profit which is available in the food and beverage industry .In fact, food is always in demand, there is no worry for our business to shut down. With the existence of the expertise, the highly commitment, the high-qualified franchisor team and more knowledge in the aspects of this business, it will reduce the risk of failure. In order to achieve the purposed of this business, we are oriented to cope with the constantlychanging needs of the customers. It is also important to adapt their expectations and demands.